Introducing intrapreneurship management concept in function of improving organizational performance - Natasha Ristovska; Daliborka Blazheska; Sashko Gramatnikovski (UTMS Journal of Economics, 2021)
This paper is an action research conducted in order to prove the connection of introducing intrapreneurial management concept with the motivation and productivity of employees and thus the organization's efficiency and profitability. Each employee, as individual, possess potential degree of creativity. The intrapreneurial culture and specially designed reward systems can increase motivation, satisfaction and encourage employees to use their creativity to contribute to continuous business innovations, therefore to the overall business success. The model of an innovative organization that introduces intrapreneurship concept is analyzed in this paper. The importance of adequate performance management system that supports intrapreneurial activities is highlighted. Thus, the influence of motivation on employees' creativity and overall innovation processes is elaborated. Finally, the need of fostering intrapreneurship is presented. The research is supported by case study of a multinational organization in the service industry in N. Macedonia where survey was conducted among 90 employees. The results confirm that intrapreneurship concept should be implemented in service organizations in order to increase the creativity and motivation of employees to be involved in innovation processes and therefore contribute to business prosperity and improved performance.
Keywords: M21; M10; L26; L83; 330; intrapreneurship; creativity; innovation; motivation; productivity; performance